Pengaruh Tingkat Pendidikan Terhadap Kualitas Laporan Keuangan Berbasis SAK EMKM Dengan Sistem Informasi Akuntansi Sebagai Variabel Moderasi : Studi Kasus Pada Coffee Shop Kota Kediri - Sinky, Sita Prasti; Luayyi, Sri; Fauziyah, Fauziyah (Jurnal Ekonomi, Bisnis dan Manajemen, 2026)
This study aims to analyze the effect of education level on the quality of financial statements based on SAK EMKM, with accounting information systems as a moderating variable, focusing on coffee shop micro, small, and medium enterprises (MSMEs) in Kediri City, Indonesia. A quantitative approach was employed using primary data collected through structured questionnaires distributed to 32 business owners or financial managers selected by purposive sampling. Data were analyzed using descriptive statistics, classical assumption tests, and Moderated Regression Analysis (MRA) with SPSS software.The results indicate that education level has a positive and significant effect on the quality of financial statements, suggesting that higher educational attainment enhances accounting understanding and compliance with SAK EMKM. However, accounting information systems were found to weaken this relationship, indicating that system complexity, limited digital literacy, and insufficient technical training may reduce the effectiveness of education in improving financial reporting quality. These findings highlight that improving financial reporting quality among MSMEs requires not only higher educational capacity but also appropriate technological support and continuous technical assistance. This study contributes to the accounting literature by emphasizing the contextual role of accounting information systems in shaping the relationship between human capital and financial reporting quality in MSMEs.